Elastisitas Hukum Islam; Kajian Teori Double Movement Fazlur Rahman - Adib Hamzawi (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2016)
Muslims believe that the whole movement of his life step should be within the framework of the religious syari’ah. There can be no speech, movement, and even empty thinking from the rule of Islamic law or fiqh. In the midst of dynamic human life movements, of course, fiqih as a living truth rail should not be believed to be absolute. From this perspective, there is often an ambiguity of the status of fiqh in the midst of Muslims. On the one hand fiqh as shari'ah law is recognized as a universal and eternal divine message. On the other hand, fiqh is the product of intellectual work of Mujtahid. The formulation of jurisprudence is bound by methodology, scope and time, so fiqh should not be considered rigid and sustainable in the ages. In the end, two opposing currents emerge in Islamic legal thought. The first stream was pioneered by a traditionalist thinker group that holds a conservative legal footing. While the second stream pioneered Muslim thinkers who are educated in Europe and have a liberal style. The differences between the two groups stem from how to understand the Qur'anic texts as the primary reference of Islamic law. It was at this moment that a Muslim thinker named Fazlur Rahman with his neomodernism emerged. He tried to find the intersection between the two poles of thought through his monumental theory, double movement.